Variasi Waktu dan Massa Ampas Kopi Pada Leaching Minyak Dari Residu Kopi Instan - Heru Heru; Muhammad Hanif (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Robusta coffee is one of Indonesia's cultivated plant species and has high economic value. One of the processed Robusta coffee is instant coffee. Instant coffee pulp has not been utilized maximally and is only accumulate as a solid waste of coffee companies. However, because oil is insoluble in water, the oil content in the coffee pulp is still high. This study aims to study the extraction process of oil from the instant coffee pulp using Soxhlet extractor, by varying the time and mass of spent instant-coffee ground. The results showed that the percentage of extracts did not differ significantly for extraction times for 6, 7 and 8 hours. The mass variations of spent coffee ground were carried out for extraction times of 6 and 8 hours, and it was observed that the mass variations of coffee ground (15, 20 and 25 g) were generally significant for the extracts obtained, but not significant at the mass of 15 g with extraction times of 6 and 8 hours.